Prioritizing barriers of e-learning for effective teaching-learning using Fuzzy Analytic Hierarchy Process (FAHP) - Naveed, Quadri Noorulhasan; N. Qureshi, Mohamed Rafik; Alsayed, Alhuseen O.; Muhammad, AbdulHafeez; Sanober, Sumaya; Shah, Asadullah (International Conference on Intelligent Unmanned Systems (ICIUS), 2018)
E-learning has become well preferred and accepted tool in teaching-learning of higher education. This pattern of change is owing to the advancement in computer and teaching-learning methodology. The introduction of E-Learning provides the real-time flexibility of time and place. The success of E-learning depends upon many factors that must be controlled to accomplish effective E-learning outcome. Moreover, the E-learning teaching-learning process is also obstructed by several barriers. Stakeholders of E-learning must study and overcome these barriers for getting the benefit of the system. In the present research, MCDM based analytic hierarchy process in its fuzzy form has been applied to study the influence of barriers on the systems. Four main dimensions of E-Learning are selected for the study, which are, student, instructor, infrastructure, and Technology and institutional management. Twelve barriers under these dimensions are also selected to study their influences on each other. The twelve barriers of E-learning are quantified using FAHP method and prioritized in terms of control the barriers. The prioritization of such barriers will help the stakeholders to control the E-learning teaching-learning system.